Thriving, not just surviving: Using positive psychology to build psychological wellbeing in pre-tertiary students - O'Neill, Ruth; James, Trixie; Hof, Sara; Johnston, Katrina; Dzator, Michael (Journal of University Teaching and Learning Practice, 2024)
The significance of psychological wellbeing for student success is under-investigated, particularly for pre-tertiary Enabling students (those traditionally under-represented in higher education). Positive Psychology Interventions (PPIs) have proven effective in enhancing wellbeing but are rarely integrated into university courses. This study explored a PPI, Be Positive, a 12-week program, designed to teach students strategies and techniques to help them re-frame their thinking about themselves and their academic pursuits. The program was evaluated with 37 Enabling students who completed weekly wellbeing questionnaires alongside self-reports about their study-related wellbeing. Results indicated fluctuating but generally positive levels of wellbeing throughout the program, with the highest levels recorded in the final weeks. A significant number of participants (79%) reported positive wellbeing by the program end, contrasting typical declines in student wellbeing during university terms. Thematic analysis of student reflections on how the program supported their wellbeing identified four key areas: affective balance, adaptive psychological resources, self-regulation, and positive implications for both academic and personal life. The findings suggest that PPIs like Be Positive can offer a proactive approach to mental health, equipping students with tools for resilience and emotional regulation, thereby enhancing wellbeing and potentially subsequent academic performance.